2022
DOI: 10.1097/jom.0000000000002689
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors at the Periconceptional Period and the Occurrence of Cleft Lip and Palate in a Midwest Brazil Population

Abstract: Objective: To investigate the association between periconceptional environmental exposures and the occurrence of cleft lips and palates. Methods: This case-control study analyzed 150 mothers of children with cleft lips and palates living in the same city as 250 mothers whose children did not present with this malformation (controls). Environmental exposure data were gathered through a questionnaire (Latin American Collaborative Study of Congenital Malformations methodology). Results: Multivariate analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…Related studies have shown that lowincome families, pesticide exposure history, smoking during pregnancy, gestational diabetes, and heavy metal exposure history such as Pb(lead), Cd (cadmium), and Sr(strontium) are all high-risk risks of OFCs. The reasonable supplement of vitamin, potassium and calcium during pregnancy is a protective factor to reduce the occurrence of OFCs [45][46][47][48]. However, due to the limitation of the number of studies included in this paper and the difference in the quality of the literature, Hansen CA et al only adjusted the age of pregnancy and lacked the adjustment of many related confounding factors, which would lead to deviations in the results [26].…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have shown that lowincome families, pesticide exposure history, smoking during pregnancy, gestational diabetes, and heavy metal exposure history such as Pb(lead), Cd (cadmium), and Sr(strontium) are all high-risk risks of OFCs. The reasonable supplement of vitamin, potassium and calcium during pregnancy is a protective factor to reduce the occurrence of OFCs [45][46][47][48]. However, due to the limitation of the number of studies included in this paper and the difference in the quality of the literature, Hansen CA et al only adjusted the age of pregnancy and lacked the adjustment of many related confounding factors, which would lead to deviations in the results [26].…”
Section: Discussionmentioning
confidence: 99%